The NOW database of fossil mammals - Žliobaitė, Indrė (2023)
NOW (New and Old Worlds) is a global databaseof fossil mammal occurrences, currently containing around68,000 locality-species entries. The database spans the last66 million years, with its primary focus on the last 23 millionyears. Whereas the database contains records from allcontinents, the main focus and coverage of the databasehistorically has been on Eurasia. The database includesprimarily, but not exclusively, terrestrial mammals. It coversa large part of the currently known mammalian fossil record,focusing on classical and actively researched fossil localities.The database is managed in collaboration with an internationaladvisory board of experts. Rather than a static archive,it emphasizes the continuous integration of new knowledgeof the community, data curation, and consistency ofscientific interpretations. The database records speciesoccurrences at localities worldwide, as well as ecologicalcharacteristics of fossil species, geological contexts oflocalities and more. The NOW database is primarily usedfor two purposes: (1) queries about occurrences of particulartaxa, their characteristics and properties of localities in thespirit of an encyclopedia; and (2) large scale research andquantitative analyses of evolutionary processes, patterns,reconstructing past environments, as well as interpretingevolutionary contexts. The data are fully open, no logging inor community membership is necessary for using the data forany purpose.